Problem Based Learning Pengembangan Lembar Kerja Peserta Didik Untuk Meningkatkan Hasil Belajar - Safitri, Tiara; Yanti, Iing Rika; Rahmi, Aidhia (Universitas PGRI Sumatera Barat, 2020)
At this time many learning models are used, where students learn, work, and interact in small groups. Based on the results of observations at SMAN 9 Padang class XI MIPA, students need a development of teaching materials that can help students to solve problems in learning. The purpose of this research is to develop teaching materials in the form of student worksheet based on problem based learning that are valid & practical for class XI MIPA SMAN 9 Padang.This type of research is included in development research or Research and Development (R&D) with a 4-D model. The 4-D model consists of four stages, namely define, design, develop, and disseminate. At the disseminate stage, it is not carried out due to time and cost limitations. In this study, the research instruments used were validity and practicality sheets. The results showed that the PBL-based LKPD developed was categorized as valid with a percentage of 85.93%. Then the PBL-based LKPD developed was categorized as very practical with a percentage of 85.32%.